A spherical lithium / sodium ion battery copper oxalate and its decomposition derivative negative electrode material
The preparation of spherical copper oxalate material through solubilizing thermal method without surfactant was solved, and the problem of insufficient capacity and rate performance of the negative electrode material of lithium/sodium ion battery was achieved, higher electrochemical performance and cycle stability were achieved, and lithium/ The development of sodium ion batteries.
Patent Information
- Application Number
- CN202211230006.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-09
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-10-09
AI Technical Summary
The existing lithium/sodium ion battery negative electrode materials have low theoretical capacity and poor rate performance, and the micro-nano structure regulation of transition metal oxalate materials is limited, which limits its application in batteries.
The spheric copper oxalate and its derivatives were prepared by surfactant-free solvothermal method. By controlling the hydrolysis and particle nucleation process of oxalic acid, a three-dimensional structure is formed to improve the electrochemical performance of lithium/sodium ion batteries.
It significantly improves the reversible capacity and rate performance of lithium/sodium ion batteries, extends the cycle stability, avoids the use of organic additives, and enhances the electrochemical lithium/sodium storage performance of the material.
Smart Images

Figure CN115504875B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a quasi-spherical lithium / sodium ion battery copper oxalate and a derivative product negative electrode material thereof, belonging to the technical field of lithium ion batteries. Background Art
[0002] In recent years, with the continuous development of new energy vehicles and secondary energy storage markets, the demand for energy storage equipment has shown an exponential growth. As a new type of high-energy green chemical power source, lithium / sodium ion batteries have been widely used due to their long cycle life, high safety performance, and environmental protection. At present, the negative electrode materials of commercial lithium / sodium ion batteries are mostly based on graphite carbon materials, but the lithium storage form of their intercalation reaction also leads to a low theoretical capacity of the material (~370 mAh g -1 ) and poor rate performance. This results in high-power, large-capacity lithium / sodium-ion power batteries in electric vehicles being plagued by volume density, price, and safety issues, and lithium / sodium-ion batteries still face great challenges. Therefore, better exploration of the next generation of negative electrode materials is crucial to breaking through battery performance barriers. Compared with many other alternative materials, metal oxalates based on diversified lithium storage reactions have the advantages of high energy density, excellent cycle performance, abundant resources, environmental friendliness, and high safety. However, problems such as the material's own low electronic conductivity, slow lithium / sodium ion diffusion rate, and high irreversible capacity have also seriously limited its practical application.
[0003] At present, in view of the above defects, from the perspective of material micro-nanostructure design, the differentiated morphology leads to the unique physical and chemical properties of the material, which has the following effects on its electrochemical performance: 1. Different lithium / sodium ion diffusion distances directly affect the rate performance of the material; 2. The stability of the structure plays a vital role in the material cycle stability, and plasticity and creep can reduce the structural instability caused by the volume effect; 3. The higher specific surface area increases the number of active sites in the material, provides more lithium / sodium ion diffusion channels, and enhances the electrochemical reaction capacity. It can be seen that the optimization of the micro-nanostructure of the material can screen out particle morphology with short lithium / sodium ion diffusion distance, multiple internal migration channels, and stable structure, so as to obtain higher reversible capacity, excellent rate and cycle performance of the material. However, the micro-nanostructure regulation of transition metal oxalate negative electrode materials is still in the controllable preparation research of two-dimensional structures such as rods, rods, fibers, and sheets, and the process of optimizing lithium / sodium ion diffusion is still limited. The present invention starts with the design of the three-dimensional structure of material particles. By regulating the form of buffer solvent addition during the synthesis of copper oxalate materials, an innovative synthesis process for three-dimensional spherical copper oxalate and its decomposition derivatives without the addition of surfactant is proposed. With the help of special structural characteristics, the electrochemical performance of the material in lithium / sodium ion battery energy storage is improved. Summary of the invention
[0004] In view of the shortcomings of the above-mentioned technologies, the present invention provides a quasi-spherical lithium / sodium ion battery copper oxalate and its derivative negative electrode materials based on the problems of single copper oxalate particle structure, inevitable and difficult to handle organic additives or surfactants in synthesis. The present invention adopts a simple solvothermal technology to inhibit the copper oxalate complex - Cu(C2O4) n -2(n-1) The formation of oxalic acid is controlled, the hydrolysis process of oxalic acid and the nucleation and growth process of material particles are controlled, and spherical copper oxalate and its derivatives are prepared.
[0005] The invention adds soluble copper salt into deionized water, stirs until completely dissolved, and then adds a certain amount of dilute acid solution to obtain a copper salt solution; prepares deionized water and anhydrous ethanol into a mixed solution, adds oxalic acid solid, stirs until completely dissolved, and then adds the oxalic acid solution into the copper salt solution, controls reaction process parameters, and after the reaction is completed and naturally cooled, filters and washes, and vacuum dries to obtain a quasi-spherical copper oxalate material; and under different atmosphere conditions, places the obtained quasi-spherical copper oxalate material in a vacuum tube furnace to control the sintering temperature and sintering time to obtain a quasi-spherical copper oxalate decomposition derivative product.
[0006] The specific preparation steps of the present invention are as follows:
[0007] (1) Add soluble copper salt to deionized water and stir until completely dissolved to obtain a copper salt solution with a mass fraction of 5% to 25%, then add a dilute acid solution with a volume fraction of 5% to 20%, and continue stirring for 15 to 30 minutes to obtain a copper salt solution with a pH of 0.01 to 2;
[0008] (2) Deionized water and anhydrous ethanol are prepared into a mixed solution in a volume ratio of 1:1 to 9:1, oxalic acid solid is added, and stirred until completely dissolved to obtain an oxalic acid solution with a mass fraction of 1% to 20%, wherein the molar ratio of oxalic acid solid to soluble copper salt solid is 1:1 to 1:3, and then the oxalic acid solution is added to the above copper salt solution, and the addition rate is controlled at 1 to 30 mL / min, the reaction temperature is 30 to 100°C, and stirring is continued for 2 to 24 hours. After the reaction is completed and naturally cooled, it is filtered and washed, and vacuum dried for 12 to 24 hours to obtain a spherical copper oxalate material;
[0009] (3) Under different atmosphere conditions, the spherical copper oxalate material obtained in step (2) is placed in a vacuum tube furnace and sintered at 150 to 500° C. for 1 to 6 h to obtain a copper oxalate decomposition derivative product.
[0010] The beneficial effects of the present invention are as follows: the present invention prepares a spherical lithium / sodium ion battery copper oxalate and its derivative negative electrode material by regulating a simple solvent thermal method. The present invention controls the hydrolysis process of oxalic acid by adding an acid solution, thereby reducing the C2O4 -2 The content of CuC2O4 + (n-1) C2O4 inhibits the reaction -2 →Cu(C2O4) n -2(n-1) Control the copper oxalate complex - Cu(C2O4) n -2(n-1) The generation of the material particle nucleation and growth process can be controlled to prepare spherical copper oxalate and its derivatives, effectively avoiding the addition of organic surfactants. In addition, the construction of the three-dimensional structure of the material is conducive to the transmission of lithium ions and electron migration during the charge and discharge process, which can significantly improve the electrochemical lithium / sodium storage performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 It is the CuC2O4 prepared in Example 1 of the present invention. x X-ray diffraction (XRD) pattern of H2O material;
[0012] Figure 2 The CuC2O4 prepared in Examples 1, 2 and 3 of the present invention is x Scanning electron microscope (SEM) image of H2O material;
[0013] Figure 3 The CuC2O4 prepared in Examples 5 and 6 of the present invention. x Scanning electron microscopy (SEM) images of H2O decomposition-derived products;
[0014] Figure 4 The CuC2O4 prepared in Examples 1 and 2 of the present invention is x Cycling performance diagram of H2O negative electrode material in lithium-ion battery system;
[0015] Figure 5 The CuC2O4 prepared in Examples 3 and 4 of the present invention is x Rate performance diagram of H2O negative electrode material in sodium ion battery system;
[0016] Figure 6 It is CuC2O4 prepared in Example 5 of the present invention. x The charge and discharge curves of H2O decomposition derivatives as negative electrode materials at different rates in a lithium-ion battery system. DETAILED DESCRIPTION
[0017] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to the described contents.
[0018] Example 1: In this example, a method for preparing a spherical lithium / sodium ion battery copper oxalate and its derivative negative electrode material is as follows:
[0019] (1) Add copper sulfate to deionized water and stir until it is completely dissolved to obtain a copper salt solution with a mass fraction of 5%, then add a dilute sulfuric acid solution with a volume fraction of 20%, and continue stirring for 15 minutes to obtain a copper sulfate solution with a pH of 0.01;
[0020] (2) Deionized water and anhydrous ethanol are prepared into a mixed solution in a volume ratio of 1:1, and oxalic acid solid is added and stirred until it is completely dissolved to obtain an oxalic acid solution with a mass fraction of 20%, wherein the molar ratio of oxalic acid solid to copper sulfate solid is 1:1, and then the oxalic acid solution is added to the copper sulfate solution in step (1), and the addition rate is controlled at 1 mL / min, the reaction temperature is 60°C, and stirring is continued for 8 h. After the reaction is completed and naturally cooled, the mixture is filtered and washed, and then dried in vacuum for 12 h to obtain a spherical copper oxalate material CuC2O4· x H2O;
[0021] (3) Under argon atmosphere, the spherical copper oxalate material obtained in step (2) is placed in a vacuum tube furnace and sintered at 150° C. for 3 h to obtain cuprous oxide, a decomposition product of copper oxalate.
[0022] Weigh 0.3 g of the spherical copper oxalate CuC2O4 prepared in this example. x H2O material, 0.15g acetylene black, and 0.05g polyvinylidene fluoride (PVDF) were put into a mortar and ground for 30 minutes, and then 1mL N-methyl-2-pyrrolidone solution was added and grinding was continued for 20 minutes. The viscous mixture was evenly coated on the copper foil, and then preliminarily dried at 80°C for 15 minutes, and then dried in a vacuum oven at 80°C for 12 hours. After that, the copper foil was rolled and cut into discs with a diameter of 14 mm to obtain the electrode.
[0023] In a glove box filled with argon (O2 content <1ppm, water content <1ppm), the electrode, separator, lithium sheet and nickel foam mesh were assembled into button cells by conventional methods, and the battery electrochemical performance was tested on a constant current charge and discharge system at a current density of 1C=1000 mA / g.
[0024] The spherical copper oxalate CuC2O4 prepared in this example x The X-ray diffraction pattern of H2O material is as follows Figure 1 As shown in the scanning electron microscope image Figure 2As shown in a, the cycle performance diagram in the lithium-ion battery system is as follows Figure 4 As shown. Figure 1 It can be seen that the material prepared in this embodiment is pure phase copper oxalate CuC2O4· x H2O material. Figure 2 It can be seen from a that the material prepared in this example is spherical particles, and the secondary particle size is 3-5 μm. Figure 4 It can be seen that the material prepared in this example shows excellent cycle performance as a negative electrode material for lithium-ion batteries, and still has ~500 mAh g after 60 charge and discharge cycles. -1 The discharge capacity.
[0025] Example 2: In this example, a method for preparing a spherical lithium / sodium ion battery copper oxalate and its derivative negative electrode material is as follows:
[0026] (1) Add copper chloride to deionized water and stir until it is completely dissolved to obtain a copper salt solution with a mass fraction of 25%, then add a dilute sulfuric acid solution with a volume fraction of 5%, and continue stirring for 30 minutes to obtain a copper chloride solution with a pH of 0.5;
[0027] (2) Deionized water and anhydrous ethanol were prepared into a mixed solution in a volume ratio of 9:1, and oxalic acid solid was added and stirred until it was completely dissolved to obtain an oxalic acid solution with a mass fraction of 20%, wherein the molar ratio of oxalic acid solid to copper chloride solid was 1:3. The oxalic acid solution was then added to the copper chloride solution at a rate of 30 mL / min and a reaction temperature of 100°C. The mixture was stirred for 2 h. After the reaction was completed and cooled naturally, the mixture was filtered and washed, and dried in vacuum for 12 h to obtain a spherical copper oxalate material CuC2O4· x H2O;
[0028] (3) Under oxygen atmosphere, the spherical copper oxalate material obtained in step (2) is placed in a vacuum tube furnace and sintered at 500° C. for 6 h to obtain copper oxide, a decomposition product of copper oxalate.
[0029] Weigh 0.3 g of the spherical copper oxalate CuC2O4 prepared in this example. x H2O material, 0.15g acetylene black, and 0.05g polyvinylidene fluoride (PVDF) were put into a mortar and ground for 30 minutes, and then 1mL N-methyl-2-pyrrolidone solution was added and grinding was continued for 20 minutes. The viscous mixture was evenly coated on the copper foil, and then preliminarily dried at 80°C for 15 minutes, and then dried in a vacuum oven at 80°C for 12 hours. After that, the copper foil was rolled and cut into discs with a diameter of 14 mm to obtain the electrode.
[0030] In a glove box filled with argon (O2 content <1ppm, water content <1ppm), the electrode, separator, lithium sheet and nickel foam mesh were assembled into button cells by conventional methods, and the battery electrochemical performance was tested on a constant current charge and discharge system at a current density of 1C=1000 mA / g.
[0031] The spherical copper oxalate CuC2O4 prepared in this example x Scanning electron microscopy images of H2O materials Figure 2 b, the cycle performance diagram in the lithium-ion battery system is as follows Figure 4 As shown. Figure 2 b It can be seen that the secondary particles of the material prepared in this example are spherical particles, which are formed by the accumulation of primary nanoparticles. Figure 4 It can be seen that the material prepared in this example shows excellent cycle performance as a negative electrode material for lithium-ion batteries, and still has ~500 mAh g after 60 charge and discharge cycles. -1 The discharge capacity.
[0032] Example 3: In this example, a method for preparing a spherical lithium / sodium ion battery copper oxalate and its derivative negative electrode material is as follows:
[0033] (1) Add copper nitrate to deionized water and stir until it is completely dissolved to obtain a copper salt solution with a mass fraction of 5%, then add a dilute acid solution with a volume fraction of 20%, and continue stirring for 30 minutes to obtain a copper nitrate solution with a pH of 0.5;
[0034] (2) Deionized water and anhydrous ethanol were prepared into a mixed solution in a volume ratio of 1:1, and oxalic acid solid was added and stirred until it was completely dissolved to obtain an oxalic acid solution with a mass fraction of 10%, wherein the molar ratio of oxalic acid solid to copper nitrate solid was 1:1. The oxalic acid solution was then added to the copper nitrate solution at a rate of 10 mL / min and a reaction temperature of 50 °C. The stirring was continued for 2 h. After the reaction was completed and cooled naturally, the mixture was filtered and washed, and then dried in vacuum for 12 h to obtain a spherical copper oxalate material CuC2O4· x H2O;
[0035] (3) In an anhydrous air atmosphere, the spherical copper oxalate material obtained in step (2) is placed in a vacuum tube furnace and sintered at 300° C. for 6 h to obtain copper oxide, a decomposition product of copper oxalate.
[0036] Weigh 0.3 g of the spherical copper oxalate CuC2O4 prepared in this example. xH2O material, 0.15g acetylene black, and 0.05g polyvinylidene fluoride (PVDF) were put into a mortar and ground for 30 minutes, and then 1mL N-methyl-2-pyrrolidone solution was added and grinding was continued for 20 minutes. The viscous mixture was evenly coated on the copper foil, and then preliminarily dried at 80°C for 15 minutes, and then dried in a vacuum oven at 80°C for 12 hours. After that, the copper foil was rolled and cut into discs with a diameter of 14 mm to obtain the electrode.
[0037] In a glove box filled with argon (O2 content <1ppm, water content <1ppm), the electrode, diaphragm, sodium sheet and nickel foam mesh were assembled into button cells by conventional methods, and the battery electrochemical performance was tested on a constant current charge and discharge system at a current density of 1C=1000 mA / g.
[0038] The spherical copper oxalate CuC2O4 prepared in this example x Scanning electron microscopy images of H2O materials Figure 2 c, the rate performance diagram in the sodium ion battery system is as follows Figure 5 As shown. Figure 2 c It can be seen that the material prepared in this example is spherical particles with a particle size of 5-10 μm, and the particles are gradually grown from primary particles. Figure 5 It can be seen that the material prepared in this example shows excellent rate performance as a negative electrode material for sodium ion batteries at 0.02, 0.1, 0.2, 0.5, 1, and 3 A g -1 The current density of ~500, 375, 310, 290, 235, and 150 mAh g -1 The discharge capacity.
[0039] Example 4: In this example, a method for preparing a spherical lithium / sodium ion battery copper oxalate and its derivative negative electrode material is as follows:
[0040] (1) Add copper sulfate to deionized water and stir until it is completely dissolved to obtain a copper salt solution with a mass fraction of 25%, then add a dilute acid solution with a volume fraction of 20%, and continue stirring for 30 minutes to obtain a copper sulfate solution with a pH of 0.1;
[0041] (2) Deionized water and anhydrous ethanol were prepared into a mixed solution in a volume ratio of 5:1, and oxalic acid solid was added and stirred until it was completely dissolved to obtain an oxalic acid solution with a mass fraction of 20%, wherein the molar ratio of oxalic acid solid to copper sulfate solid was 1:2. The oxalic acid solution was then added to the copper salt solution at a rate of 10 mL / min and a reaction temperature of 80°C. Stirring was continued for 12 h. After the reaction was completed and cooled naturally, the mixture was filtered and washed, and then dried in vacuum for 12 h to obtain a spherical copper oxalate material CuC2O4· x H2O;
[0042] (3) Under hydrogen atmosphere, the spherical copper oxalate material obtained in step (2) is placed in a vacuum tube furnace and sintered at 150° C. for 3 h to obtain a mixture of cuprous oxide and elemental copper, which are decomposition products of copper oxalate.
[0043] Weigh 0.3 g of the spherical copper oxalate CuC2O4 prepared in this example. x H2O material, 0.15g acetylene black, and 0.05g polyvinylidene fluoride (PVDF) were put into a mortar and ground for 30 minutes, and then 1mL N-methyl-2-pyrrolidone solution was added and grinding was continued for 20 minutes. The viscous mixture was evenly coated on the copper foil, and then preliminarily dried at 80°C for 15 minutes, and then dried in a vacuum oven at 80°C for 12 hours. After that, the copper foil was rolled and cut into discs with a diameter of 14 mm to obtain the electrode.
[0044] In a glove box filled with argon (O2 content <1ppm, water content <1ppm), the electrode, diaphragm, sodium sheet and nickel foam mesh were assembled into button cells by conventional methods, and the battery electrochemical performance was tested on a constant current charge and discharge system at a current density of 1C=1000 mA / g.
[0045] The spherical copper oxalate CuC2O4 prepared in this example x The rate performance of H2O materials in sodium ion battery system is shown in the figure Figure 5 As shown. Figure 5 It can be seen that the material prepared in this example shows excellent rate performance as a negative electrode material for sodium ion batteries at 0.02, 0.1, 0.2, 0.5, 1, and 3 A g -1 The current density was ~350, 175, 150, 140, 120, and 75 mAh g -1 The discharge capacity.
[0046] Example 5: In this example, a method for preparing a spherical lithium / sodium ion battery copper oxalate and its derivative negative electrode material is as follows:
[0047] (1) Add copper sulfate to deionized water and stir until it is completely dissolved to obtain a copper salt solution with a mass fraction of 15%, then add a dilute acid solution with a volume fraction of 10%, and continue stirring for 15 minutes to obtain a copper sulfate solution with a pH of 1;
[0048] (2) Deionized water and anhydrous ethanol were prepared into a mixed solution in a volume ratio of 1:1, and oxalic acid solid was added and stirred until it was completely dissolved to obtain a 5% oxalic acid solution, wherein the molar ratio of oxalic acid solid to copper sulfate solid was 1:1. The oxalic acid solution was then added to the copper sulfate solution at a rate of 10 mL / min and a reaction temperature of 60°C. Stirring was continued for 2 h. After the reaction was completed and cooled naturally, the mixture was filtered and washed, and then dried in vacuum for 12 h to obtain a spherical copper oxalate material CuC2O4· x H2O;
[0049] (3) Under nitrogen atmosphere, the spherical copper oxalate material obtained in step (2) is placed in a vacuum tube furnace and sintered at 270° C. for 3 h to obtain cuprous oxide, a decomposition product of copper oxalate.
[0050] Weigh 0.3 g of the cuprous oxide material derived from the decomposition of copper oxalate prepared in this embodiment, 0.15 g of acetylene black, and 0.05 g of polyvinylidene fluoride (PVDF), put them in a mortar, grind for 30 min, then add 1 mL of N-methyl-2-pyrrolidone solution, and continue grinding for 20 min. The viscous mixture is evenly coated on the copper foil, and then preliminarily dried at 80 ° C for 15 min, and then dried in a vacuum oven at 80 ° C for 12 h, after which the copper foil is rolled and cut into discs with a diameter of 14 mm to obtain an electrode.
[0051] In a glove box filled with argon (O2 content <1ppm, water content <1ppm), the electrode, separator, lithium sheet and nickel foam mesh were assembled into button cells by conventional methods, and the battery electrochemical performance was tested on a constant current charge and discharge system at a current density of 1C=1000 mA / g.
[0052] The scanning electron microscope image of cuprous oxide, a derivative product of the decomposition of copper oxalate prepared in this example, is as follows: Figure 3 As shown in a, the rate performance diagram in the lithium-ion battery system is as follows Figure 5 As shown. Figure 3 a It can be seen that the material prepared in this example is spherical particles with a particle size of ~10μm, and the material is agglomerated from primary nanoparticles. Figure 5 It can be seen that the material prepared in this example exhibits excellent rate performance as a negative electrode material for lithium-ion batteries at 0.1, 0.5, 1, 2, 3, and 5 A g -1The current density of ~500, 450, 400, 380, 350, 325 mAh g -1 The discharge capacity.
[0053] Example 6: In this example, a method for preparing a spherical lithium / sodium ion battery copper oxalate and its derivative negative electrode material is as follows:
[0054] (1) Add copper acetate to deionized water and stir until it is completely dissolved to obtain a copper salt solution with a mass fraction of 5%, then add a dilute acid solution with a volume fraction of 10%, and continue stirring for 20 minutes to obtain a copper acetate solution with a pH of 2;
[0055] (2) Deionized water and anhydrous ethanol were prepared into a mixed solution in a volume ratio of 1:1, and oxalic acid solid was added and stirred until it was completely dissolved to obtain an oxalic acid solution with a mass fraction of 1%, wherein the molar ratio of oxalic acid solid to copper acetate solid was 1:2. The oxalic acid solution was then added to the copper acetate solution at a rate of 5 mL / min and a reaction temperature of 80°C. Stirring was continued for 12 h. After the reaction was completed and cooled naturally, the mixture was filtered and washed, and then dried in vacuum for 24 h to obtain a spherical copper oxalate material CuC2O4· x H2O;
[0056] (3) In a mixed atmosphere of hydrogen and argon, the spherical copper oxalate material obtained in step (2) is placed in a vacuum tube furnace and sintered at 400° C. for 1 h to obtain a copper element derived from the decomposition of copper oxalate.
[0057] The scanning electron microscope image of the copper element of the copper oxalate decomposition derivative product prepared in this example is as follows: Figure 3 As shown in b. Figure 3 b It can be seen that the material prepared in this example is spherical particles with a particle size of ~10μm, and the material is formed by the agglomeration of primary nanoparticles.
[0058] The specific implementation modes of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A method for preparing a spherical lithium / sodium ion battery copper oxalate and its decomposition derivative negative electrode material, It is characterized in that The specific steps are as follows: (1) adding a soluble copper salt to deionized water, stirring until completely dissolved to obtain a copper salt solution with a mass fraction of 5% to 25%, then adding a dilute acid solution with a volume fraction of 5% to 20%, and continuously stirring for 15 to 30 minutes to obtain a copper salt solution with a pH of 0.01 to 2, wherein the soluble copper salt in step (1) is one of copper sulfate, copper chloride, copper nitrate, and copper acetate, or a mixture of any of the above; (2) preparing a mixed solution of deionized water and anhydrous ethanol in a volume ratio of 1:1 to 9:1, adding oxalic acid solid, stirring until completely dissolved to obtain an oxalic acid solution with a mass fraction of 1% to 20%, then adding the oxalic acid solution to the copper salt solution of step (1), controlling the addition rate to 1 to 30 mL / min, the reaction temperature to 30 to 100°C, and continuously stirring for 2 to 24 hours. After the reaction is completed and naturally cooled, filtering and washing, vacuum drying for 12 to 24 hours, obtaining a spherical copper oxalate material, and using it as a negative electrode material for lithium / sodium ion batteries, wherein the molar ratio of the oxalic acid solid added in step (2) to the soluble copper salt solid added in step (1) is 1:1 to 1:3; (3) Under different atmosphere conditions, the spherical copper oxalate material obtained in step (2) is placed in a vacuum tube furnace and sintered at 150-500° C. for 1-6 hours to obtain a copper oxalate decomposition derivative product, which is used as a negative electrode material for lithium / sodium ion batteries; The decomposition derivative of copper oxalate obtained after sintering in step (3) is one of copper oxide, cuprous oxide, and copper element, or a mixture of any of several of them. The different atmospheres in step (3) are one of argon, nitrogen, oxygen, anhydrous air, and hydrogen, or a mixture of any of several gases.
